Education on breastfeeding, lactation management, complementary feeding and infant stimulation in Karangpoh, Gresik Regency - Hamidah, Siti; Inayah, Zufra (Universitas Muhammadiyah Magelang, 2021)
Community service is carried out in 4 areas of Karangpoh Village, Gresik Regency, East Java in February-June 2021. The problem that occurs is the presence of malnutrition in Karangpoh Village. The objectives of this community service are: (1) providing learning about lactation management, complementary feeding and infant stimulation, (2) knowing the impact of activities in the form of knowledge and skills of PKK members on the delivered materials. The method of community service is by conducting workshops with 80 participants. The results of the service carried out are the average score of breastfeeding practice after the workshop (86.80) is better than before (48.52), and the average score of baby (3-6 months) stimulation skills after the workshop (87.89) is also better than before (53.88). This community service has implications for increasing exclusive breastfeeding coverage, optimizing complementary feeding, and preventing growth delays in infants and children.